Studi Keanekaragaman dan Persepsi Masyarakat Terhadap Hutan Mangrove di Desa Tiwatobi Kecamatan Ile Mandiri Kabupaten Flores Timur Provinsi Nusa Tenggara Timur - Alfira Defni Bulu Tuan; Ludji Michael Riwu Kaho; Mamie E. Pellondou (Wana Lestari, 2022)
This study aimed to determine the level of diversity and community perception of the existence of mangrove vegetation in Tiwatobi village, East Flores regency, East Nusa Tenggara province. This research is survey research. Based on the data collection techniques, this study employed observation techniques on 13 Mangrove plots measuring 2m x 2m, 5m x 5m, and 10m x 10m to determine the diversity of mangrove vegetation. Furthermore, the interview technique and the distribution of the questionnaire to 82 respondents based on the Slovin formula were carried out to specify community perceptions of mangrove vegetation. The results revealed five types of mangroves grouped into three families. The most elevated relative density at the tree level was RhyzophotaMucronata (29.94), and the lowest was Bruguiera Parviflora which was 11.98. Based on the pile and stake levels, the highest relative density values were occupied by Bruguiera Parviflora (42.59), Munto (26.03). RhyzophoraStylosa (0.0) and Bruguiera parviflora (13.01) had the lowest relative density values. Bruguiera Parviflora is the species with the highest density of all levels, with a density value of 42.59. Meanwhile, RhyzophoraStylose has the lowest relative density value of 0.0. The outcomes of this study also confirmed that the vegetation of the mangrove ecosystem in Tiwatobi village, the index of importance, diversity, and richness of mangrove vegetation with the classification of 'medium' value caused by the environmental circumstances of mangroves that grow on muddy substrates and only a few species that can grow. In addition, community activities on the coast also vandalize the mangrove ecosystem, especially for the mooring land construction to meet the family's economy. Furthermore, the community's perception of mangrove vegetation existence has a critical role in the viewpoints of physical, ecological, and economic, as evidenced by the positive response to the existence, function, and preservation of mangrove forests in Tiwatobi village.